2003
DOI: 10.1073/pnas.0530258100
|View full text |Cite
|
Sign up to set email alerts
|

Generalized singular value decomposition for comparative analysis of genome-scale expression data sets of two different organisms

Abstract: We describe a comparative mathematical framework for two genome-scale expression data sets. This framework formulates expression as superposition of the effects of regulatory programs, biological processes, and experimental artifacts common to both data sets, as well as those that are exclusive to one data set or the other, by using generalized singular value decomposition. This framework enables comparative reconstruction and classification of the genes and arrays of both data sets. We illustrate this framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
270
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(272 citation statements)
references
References 12 publications
1
270
0
1
Order By: Relevance
“…For example, the development of methods to systematically assign genes to 'regulons' 37,38 may make possible regulon-based measures of correlation that could be more sensitive and specific in their identification of analogous biological programs. The integrative use of expression data from different species is an emerging area of research [39][40][41][42][43] , and elements of these different approaches might be combined to develop additional tools. Our computational approach is also readily generalized to data on protein expression and modification 44 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the development of methods to systematically assign genes to 'regulons' 37,38 may make possible regulon-based measures of correlation that could be more sensitive and specific in their identification of analogous biological programs. The integrative use of expression data from different species is an emerging area of research [39][40][41][42][43] , and elements of these different approaches might be combined to develop additional tools. Our computational approach is also readily generalized to data on protein expression and modification 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Co-inertia analysis (CIA) is an integrative analysis method used to visualize and explore gene and protein data [1]. The generalised singular value decomposition (GSVD) [2] has shown its potential in the analysis of two transcriptome data sets. Integrative Biclustering (IBC) applies Biclustering [3] to gene and protein data.…”
Section: Methodsmentioning
confidence: 99%
“…In a related study, Vicente et al [53] found that the most influential part on the performance of ICA is the whitened transformation. Various other authors pointed the feasibility of whitening as a pre-processing step in microarray data analysis [55][56][57][58][59][60][61]. Whitening is performed via singular value decomposition (SVD) on the centered 3 data matrix X:…”
Section: Compaction Stagementioning
confidence: 99%